Synthesis of axially chiral biaryl thioglycosides through thiosugar-directed Pd-catalyzed asymmetric C–H activation. Issue 80 (17th September 2021) - Fatthalla, Maha; Grimblat, Nicolas; Brachet, Etienne; Alami, Mouad; Gandon, Vincent; Le Bideau, Franck; Messaoudi, Samir
Abstract : An atroposelective Fujiwara–Moritani reaction towards the synthesis of alkenylthioglycoside is reported. β-thioglucose moiety is used both as a directing group for the C–H bond activation and as a chiral source inducing axial chirality. Abstract : Herein we report for the first time that the thiosugar moiety can be used both as a directing group enabling the regioselective activation of a C–H bond of biaryl scaffolds and as a chiral source inducing axial chirality. Our approach enables the easy generation of complex thioglycoside atropoisomers, thus paving the way to new products of potential biological interest.